Hiring by start-ups and regional labor supply - Lisa Bellmann; Udo Brixy (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2018)
Young firms find it difficult to attract (skilled) workers. Using linked employer-employee data for Germany we investigate how local labor market conditions affect the hiring success of young firms. In a first step, we estimate the probability of the founder becoming an employer. In a second step we analyze how local conditions influence the probability of hiring skilled human capital. The results indicate a positive relationship between the local unemployment level and the hiring probability of young firms. – – Junge Firmen haben oft Schwierigkeiten (qualifizierte) Beschäftigte einzustellen. Basierend auf einem Linked Employer-Employee Datensatz für Deutschland untersuchen wir den Einfluss regionale Arbeitsmarktbedingungen auf die Einstellungschancen junger Firmen. Im ersten Schritt schätzen wir die Wahrscheinlichkeit, dass ein Gründer Beschäftigte einstellt. Im zweiten Schritt verwenden wir ein Heckman-Selektionsmodell und analysieren, wie regionale Bedingungen die Einstellungswahrscheinlichkeit von qualifizierten Beschäftigten beeinflussen. Die Ergebnisse zeigen einen positiven Zusammenhang zwischen der regionalen Höhe der Arbeitslosigkeit und der Einstellungswahrscheinlichkeit junger Firmen.
Keywords: D22; L26; R12; 330; Entrepreneurship; hiring; skilled workers; regional labor supply